Biodynamics of HCV infection in haemodialysis patients in Pahang - Mustafa Mahmoud, Mohammed Imad Al-Deen; Abdul Majid, Mohammed Saad; Hamzah, Hairul Aini; Hasmani, Mohamed Hadzri (2011)

(untitled)
Hepatitis C is a global disease, WHO has described it as a “viral time bomb”. In Malaysia, the sero-prevalence is 1.6%. HCV infection is frequent in patients undergoing maintenance haemodialysis, with prevalence between 8 and 10%. Hepatitis C has an adverse effect on both patient and graft survival in those who get renal transplants. There are relatively scarce reports on the natural fluctuation in viral load and alpha interferon (α-IFN) level in patients on chronic hemodialysis. Methods A longitudinal short-term three months study where 27 chronic hemodialysis patients infected with known HCV genotypes were recruited from seven hemodialysis centers in Pahang. Serum samples were collected monthly, both pre- and post-hemodialysis sessions, over a period of three months. Viral RNA was extracted from serum using QIAamp Viral RNA Extraction kit (Qiagen). The HCV viral load was measured using one step reverse transcriptase qPCR (Applied Biosystems) targeting the 5`HCV non-coding region. The serum α-IFN level was measured using commercial ELISA kit (Amersham, UK). Six biochemical liver function tests (AST, ALP, TP, albumin, ALT and TB) were also done for all pre-hemodialysis samples. Results All patients showed persistant low level viral load (Fig.1) that varied significantly over the study period (P = 0.001). HCV genotype 1 viral load was significantly higher than that of genotype 3 (Fig.2). The difference between pre- and post-haemodialysis viral load was statistically insignificant. No significant correlation between viral load and liver function status was noted. No correlation was observed between pre-haemodialysis serum α-IFN level and pre-haemodialysis viral load. The difference between pre and post-haemodialysis plasma α-IFN levels was statistically insignificant.